The contribution of Feedback Contents to the Development of Student Thesis: A case study in a Tourism School of Higher Education - Sutanto Leo (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2021)
This paper aims to investigate feedback content in order to improve the development of the student thesis. This case study used a qualitative design that used multiple data collected from nine participants (six supervisors and three supervisees). Data were obtained from the textual evidence of the student thesis drafts and in-depth interviews with nine participants. The data were analyzed by labeling, categorizing and comparing similarities and differences in order to discover patterns and identify meanings. The results show that corrective feedback on the writing mechanism makes less contribution to improving student thesis. Feedback of praise and criticism does not make a contribution to improving student thesis. Specific, descriptive and suggestive feedback on the concept and order of ideas indicates a significant improvement in the development of the student thesis. The paper concludes that the feedback received from the supervisors determines responses to improve the quality of the student thesis.